BORDER CROSSING, GENDER CONSCIOUSNESS AND EMANCIPATION IN POSTCOLONIAL NARRATIVES OF ISIDORE OKPEWHO’S CALL ME BY MY RIGHTFUL NAME, THE VICTIM AND BUCHI EMECHETA’S SECOND CLASS CITIZEN, KEHINDE - Irene AKUMBU WIBEDIMBOM (Ziglôbitha)
ABSTRACT : This article discusses the foundational factors for which the African postcolonial subject indulges in transnational or external displacement, verifying whether the purpose for their displacement has been fulfilled. The conditions of the displaced postcolonial subjects in their transnational space and their responses to the realities of this space are zoomed in by a postcolonial reading of Isidore Okpewho’s Call Me By My Rightful Name and The Victims and Buchi Emecheta’s Kehinde and Second-Class Citizen. One of the major issues handled by both writers is the question of gender consciousness and emancipation. They vividly bring to the lamb light some of the difficulties female migrants encounter out of their homeland. Though this article is linked to gender studies, which is not a field of knowledge per se, it serves as a mode of interpretation, shining light on the construction of identity, the relationship between the individual and society, and the individual and culture, which constitute some of the major elements featuring in the selected novels. Gender therefore can be characterized by political emancipation which is strongly connected with the condition of women and other subaltern subjects.